Epidemiology and risk factors for invasive fungal disease in liver transplant recipients in a tertiary transplant center. Issue 6 (22nd June 2020) - Lum, Lionel; Lee, Andie; Vu, Monica; Strasser, Simone; Davis, Rebecca
Abstract: Background: Invasive fungal disease (IFD) in liver transplant recipients causes significant morbidity and mortality. We aim to describe institutional epidemiology and risk factors for IFD in the liver transplant population. Methods: We conducted a retrospective cohort study of all adult liver transplant recipients in our institution from 2005 to October 2015 to describe the epidemiology of patients with proven and probable IFD according to the European Organization for Research and Treatment of Cancer/Mycoses Study Group criteria. To determine risk factors for IFD, a case‐control study was also conducted. Cases were defined as liver transplant recipients with proven or probable IFD, and controls were defined as liver transplant recipients without IFD. Each case was matched to two controls by age (±10 years of age), gender, and time of transplant (within one year of the case). Results: 28/554 (5.1%) patients developed IFD. Candidiasis (n = 11; 39.3%), Aspergillosis (n = 10; 35.7%), and Cryptococcosis (n = 3; 10.7%) were the most common fungal infections in the proven and probable IFD groups. Mold infections occurred in 13 (46.4%) cases. Reoperation, roux‐en‐y anastomosis, and massive intraoperative transfusion of ≥40 units of cellular blood products were major risk factors for IFD in the multivariate analysis. Conclusion: Candida and Aspergillus are the most common causes of IFD in liver transplantation in our center. There is significant overlap in risk factors for such infections post‐transplantation. In our cohort, critically ill patients with complicated perioperative course seem to predispose them to mold infections post‐transplantation, but larger studies are required to better delineate risk factors for mold infection as well as determine the efficacy and optimal duration of mold prophylaxis in liver transplantation. With increasing echinocandin use for antifungal prophylaxis, it is also important to monitor for emerging antifungal resistance.